2022
DOI: 10.1371/journal.pone.0266677
|View full text |Cite
|
Sign up to set email alerts
|

Tropical wetlands and land use changes: The case of oil palm in neotropical riverine floodplains

Abstract: Oil palm plantations are expanding in Latin America due to the global demand for food and biofuels, and much of this expansion has occurred at expense of important tropical ecosystems. Nevertheless, there is limited knowledge about effects on aquatic ecosystems near to oil palm-dominated landscapes. In this study, we used Landsat 7 ETM+, Landsat 8 OLI imagery and high-resolution images in Google Earth to map the current extent of oil palm plantations and determined prior land use land cover (LULC) in the Usuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
3
0
1
Order By: Relevance
“…Land use and land cover changes, especially propagation of oil palm plantations, have affected LPR whereas much of the SPR watershed remains lies within the Maya Biosphere Reserve. However, SPR has not escaped impacts entirely and agricultural development and wildfires have occurred in its watershed over the past 20 years, with likely consequences for nutrient loading (Camacho-Valdez et al, 2022;Ju arez-S anchez et al, 2019). Water depth was positively correlated with native fish δ 15 N signatures, and sediment depth showed the opposite trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land use and land cover changes, especially propagation of oil palm plantations, have affected LPR whereas much of the SPR watershed remains lies within the Maya Biosphere Reserve. However, SPR has not escaped impacts entirely and agricultural development and wildfires have occurred in its watershed over the past 20 years, with likely consequences for nutrient loading (Camacho-Valdez et al, 2022;Ju arez-S anchez et al, 2019). Water depth was positively correlated with native fish δ 15 N signatures, and sediment depth showed the opposite trend.…”
Section: Discussionmentioning
confidence: 99%
“…At least 172 freshwater and estuarine fish species (Soria‐Barreto et al, 2018) are reported from the basin, with ~60% of freshwater species being endemic (Elías et al, 2020). Much of the basin has been impacted by deforestation, agriculture, and natural resource extraction (Dürr, 2017; Gandin, 2012; Tapia‐Silva et al, 2015), and African palm oil plantations have propagated mainly in LPR and SPR in Guatemala (Camacho‐Valdez et al, 2022), although some of these plantations in SPR are not yet documented. In recent decades, P. pardalis , P. disjunctivus , and their hybrids have been reported in various locations (Gaitán et al, 2020; Wakida‐Kusunoki et al, 2007; Wakida‐Kusunoki & Amador del Ángel, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Entre los efectos negativos derivados de la conversión de bosques naturales en plantaciones de palma, se encuentran la pérdida de hábitats críticos para la vida silvestre, lo que a su vez contribuye a la disminución de la biodiversidad, contaminación del agua dulce, disminución del carbono orgánico del suelo y la extinción de especies [6], [19], [20]. Las principales áreas afectadas por la deforestación se encuentran principalmente en el sudeste asiático (como Indonesia y Malasia) y América Latina, cuyas consecuencias han sido nefastas tanto para el medio ambiente como para las comunidades locales [14], [21]. Como consecuencia de la deforestación y el drenaje de turberas para la plantación, se liberan grandes cantidades de carbono almacenado, aumentando las emisiones de Gases de Efecto Invernadero (GEI), y por consiguiente los efectos del cambio climático [14], [19].…”
Section: Deforestación Y Pérdida De Biodiversidadunclassified
“…The five catchments studied comprised two primary or near-primary forest catchments, a twice-selectively-logged catchment, a multiple-selectively-logged catchment and a ~20-year-old oil palm catchment. These land-use and logging histories were selected because repeat-logging and conversion to oil palm are spatially important not only within Sabah [29], but throughout ever-wet parts of SE Asia and the global tropics [35][36][37][38][39][40][41].…”
Section: Introduction and Brief Reviewmentioning
confidence: 99%